2020
DOI: 10.1088/1742-6596/1641/1/012027
|View full text |Cite
|
Sign up to set email alerts
|

Mobile-Assisted Language Learning (MALL): Students’ Perception and Problems towards Mobile Learning in English Language

Abstract: Mobile-Assisted Language Learning (MALL) is the latest learning way in the language education where applications or websites are used to facilitate students learning activities. Mobile phone has been studied years by researchers in its connection with education-related activities. This research will focus on its main purposes, they are: 1) students’ perceptions in using mobile phone in English language learning classroom activities; 2). the problem of using mobile phone to support classroom activities, especia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 9 publications
6
25
0
Order By: Relevance
“…These findings also support those of Kacetl and Klímová (2019) who indicated that the key benefits of MALL are the enhancement of the learner’s cognitive capacity, the learner’s motivation to study in both formal and informal settings, the learner’s autonomy and confidence, as well as the promotion of personalized learning, and helping low-achieving students to reach their study goals. These findings also re-echo Nuareni’s (2020) claim that the majority of the students has positive perception on the usage of MALL in learning English language. These findings are also in line with the most recent study by Jeong (2022) , who claim that MALL helped his students with access to learning contents, created flexible and self-directed learning environment, better interaction, and improved self-efficacy in English learning performance.…”
Section: Discussionsupporting
confidence: 65%
“…These findings also support those of Kacetl and Klímová (2019) who indicated that the key benefits of MALL are the enhancement of the learner’s cognitive capacity, the learner’s motivation to study in both formal and informal settings, the learner’s autonomy and confidence, as well as the promotion of personalized learning, and helping low-achieving students to reach their study goals. These findings also re-echo Nuareni’s (2020) claim that the majority of the students has positive perception on the usage of MALL in learning English language. These findings are also in line with the most recent study by Jeong (2022) , who claim that MALL helped his students with access to learning contents, created flexible and self-directed learning environment, better interaction, and improved self-efficacy in English learning performance.…”
Section: Discussionsupporting
confidence: 65%
“…At a tertiary level, educational mobile phones work as a tool for developing EFL learners' speaking skills [7] and vocabulary [32]. Moreover, the use of mobile phones is very effective for facilitating learning environments through sharing and communication among learners [26,27]. Thus, the previous studies in different EFL contexts reveal that that mobile phone is an effective tool for developing learners' language skills, regardless of the level of learners' education.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The research trends of some studies reveal that mobile-based learning is more useful and effective than conventional or traditional teaching methods [5,23]. Some other studies point out the challenges and benefits of using mobile devices in ELT, i.e., [24][25][26]. The research trends of other studies explore teachers' and learners' attitudes and beliefs regarding using mobile phones [27], as well as teaching techniques implemented thanks to mobile phones [28].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…• The problem in internet connectivity is the biggest problem students face in using MALL in English language classrooms (Nuraeni et al, 2020).…”
Section: Mallmentioning
confidence: 99%